Is personalized better: Digital advisory and productivity differentials in rice farming in Nigeria - Owusu, S.E.; Arouna, Aminou; Narrod, Clare (2023)
Personalized extension advisory deliver information that are more compatible with farmer production conditions and has a better chance of adoption and impacts. We exploit a rich four-round experimental panel data on RiceAdvice, a decision support app that provides personalized information on soil fertility management and other agricultural practices to rice farmers. We evaluate the impact of the app on technological, managerial, frontier yield, and fertilizer productivity differentials, while accounting for differences in production technologies possessed by the different treatment groups. Re sults based on the true random effects estimator suggest that exposure to RiceAdvice significantly increases the production possibilities and managerial performance of rice smallholders exposed to it (treated farmers), leading to an upward shift in the production frontier for those same farmers. Exposed farmers also have higher mean fertilizer productivity compared to the unexposed, especially when bundled with fertilizer in puts. The impacts are stronger in the early years but wanes over time. Ensuring consistent access to the app as well as fertilizer input could help sustain the gains.